2010
DOI: 10.1542/peds.2010-1536
|View full text |Cite
|
Sign up to set email alerts
|

Late-Preterm Birth and Its Association With Cognitive and Socioemotional Outcomes at 6 Years of Age

Abstract: Late-preterm birth is associated with behavioral problems and lower IQ at the age of 6, independent of maternal IQ, residential setting, and sociodemographics. Future research is needed to investigate whether these findings result from a reduction in gestational length, in utero (eg, obstetric complications) or ex-utero (eg, neonatal complications) factors marked by late-preterm birth, or some combination of these factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
127
4
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(152 citation statements)
references
References 53 publications
17
127
4
4
Order By: Relevance
“…Ces nouveau-né s sont 3 fois plus susceptibles de dé cé der avant leur premier anniversaire et 6 fois plus susceptibles de dé cé der dans leur premiè re semaine de vie [12]. La pré maturité tardive est associé e à des problè mes de comportement et un QI plus faible à l'âge de 6 ans, indé pendamment du QI maternel, du cadre de vie et des donné es sociodé mographiques [13].…”
Section: Discussionunclassified
“…Ces nouveau-né s sont 3 fois plus susceptibles de dé cé der avant leur premier anniversaire et 6 fois plus susceptibles de dé cé der dans leur premiè re semaine de vie [12]. La pré maturité tardive est associé e à des problè mes de comportement et un QI plus faible à l'âge de 6 ans, indé pendamment du QI maternel, du cadre de vie et des donné es sociodé mographiques [13].…”
Section: Discussionunclassified
“…These associations are also borne out in other studies in which resuscitation at birth, sociodemographic factors and pre-eclampsia, in particular, have been independently associated with long-term outcomes in this population. 175,199,200 Not receiving any breast milk at discharge, either expressed or by breastfeeding, was associated with disability at 2 years. The impact of breastfeeding on infant development has been widely reported, although the mechanisms for this association remain unclear in both term-born and preterm infants.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of children at 342 and 643 years showed increased cognitive impairment and behavioural problems in late preterm infants compared with babies of ≥37 weeks. However, Baron et al 44 have since published data suggesting that uncomplicated late preterm birth does not, in itself, increase the risk of later cognitive impairment.…”
Section: Long-term Outcomesmentioning
confidence: 99%
“…A large number of infants born at 32 weeks and above are offered neither neonatal nor neurodevelopmental follow-up. Many now suggest that this may not be appropriate and recommend follow-up until at least 18 months of age,38 43 48 60 but the service implications of a change in favour of this approach are substantial. Most available data are focused on late preterm birth and data for deliveries at 32–33 weeks of gestation are particularly sparse.…”
Section: Implications For Clinical Practice Research and Public Healthmentioning
confidence: 99%